Epistemology of the news industry in Arab satellite news channels - فرحاتي أمينة; قراد راضية (International Journal of Social Communication, 2025)
This article aims to investigate the knowledge process that results from the news industry process, by discussing the limits of the relationship between news epistemology and the news content industry in Arab satellite channels, while highlighting the mechanisms and strategies of news work in Arab channels, and highlighting the specificity of the news industry based on selection factors and values. news that distinguishes it from western stations. The study showed that the news industry depends on the epistemology of the news in terms of its reliance on the two processes of framing and the narrative perspective, by employing each of them the image that depends on its symbolic significance and all its dimensions and forms of employment, and the linguistic narrative that depends mainly on the employment of some vocabulary as linguistic codes that predict bias and suggestion. It is one of the unique strategies in which each channel differs from the other to deliver meaningful knowledge messages.